Balance Training as an Adjunct to Methylphenidate: A Randomized Controlled Pilot Study of Behavioral Improvement Among Children With ADHD in China - Feng, Lei; Ren, Yuanchun; Cheng, Jia; Wang, Yufeng (Frontiers in Psychiatry, 2021)
Objective: This study aimed to compare the therapeutic effects of two different approaches to attention deficit hyperactivity disorder (ADHD): 1) methylphenidate (MPH) treatment combined with balance training, and 2) MPH monotherapy. Methods: The study was based on a randomized, double-blind trial involving 27 ADHD patients. An experimental group received the treatment combining MPH and balance training, while a control group were administered just MPH. After 40 sessions of training at the 6-month mark, patients’ improvement as observed in their core symptoms and behavioral problems were compared between the experimental and control group. Results: A total of 27 patients underwent randomization, with 13 assigned to the experimental group and 14 to the control group. After the 6-month trial, the experimental group outperformed the control group in terms of teachers’ scores for inattention on the ADHD-RS-IV (19.38±2.96 vs 23.21±3.91, t=-2.854, P=0.009). The experimental group also showed greater improvement on the items involving behavior (3.14±1.46 vs 5.24±1.04, t= 1.463, P=0.026) and hyperactivity (1.92±1.19 vs 3.86±2.32, t=-2.697, P=0.012). Conclusion: In children with ADHD, the experimental group displayed a significant improvement in the symptoms and behavior associated with inattention than did the group whose treatment consisted of only MPH.